Persisting exercise ventilatory inefficiency in subjects recovering from COVID-19. Longitudinal data analysis 34 months post-discharge - Dorelli, Gianluigi; Sartori, Giulia; Fasoli, Giulia; Ridella, Nicolò; Bianchini, Nicola; Braggio, Michele; Ferrari, Marcello; Venturelli, Massimo; Carbonare, Luca Dalle; Capelli, Carlo; Grassi, Bruno; Crisafulli, Ernesto (BMC pulmonary medicine, 2024)
Background SARS-CoV-2 infection has raised concerns about long-term health repercussions. Exercise ventilatory inefficiency (EV in ) has emerged as a notable long-term sequela, potentially impacting respiratory and cardiovascular health. This study aims to assess the long-term presence of EV in after 34 months and its association with cardiorespiratory health in post-COVID patients. Methods In a longitudinal study on 32 selected post-COVID subjects, we performed two cardiopulmonary exercise tests (CPETs) at 6 months (T0) and 34 months (T1) after hospital discharge. The study sought to explore the long-term persistence of EV in and its correlation with respiratory and cardiovascular responses during exercise. Measurements included also V̇O 2peak, end-tidal pressure of CO 2 (PET CO2 ) levels, oxygen uptake efficiency slope (OUES) and other cardiorespiratory parameters, with statistical significance set at p < 0.05. The presence of EV in at both T0 and T1 defines a persisting EV in (pEV in ). Results Out of the cohort, five subjects (16%) have pEV in at 34 months. Subjects with pEV in , compared to those with ventilatory efficiency (Ev ef ) have lower values of PET CO2 throughout exercise, showing hyperventilation. Ev ef subjects demonstrated selective improvements in DL CO and oxygen pulse, suggesting a recovery in cardiorespiratory function over time. In contrast, those with pEv in did not exhibit these improvements. Notably, significant correlations were found between hyperventilation (measured by PET CO2 ), oxygen pulse and OUES, indicating the potential prognostic value of OUES and Ev in in post-COVID follow-ups. Conclusions The study highlights the clinical importance of long-term follow-up for post-COVID patients, as a significant group exhibit persistent EV in , which correlates with altered and potentially unfavorable cardiovascular responses to exercise. These findings advocate for the continued investigation into the long-term health impacts of COVID-19, especially regarding persistent ventilatory inefficiencies and their implications on patient health outcomes.